Characterization of Cd1-xZnxSe thin films deposited at low temperature by chemical route - Hankare, P. P.; Chate, P. A.; Asabe, M. R.; Delekar, S. D.; Mulla, Imtiaz S.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2006)
Optoelectronic technologically important pseudo-binary Cd1-xZnxSe thin films with a variable composition ( 0 < x < 1) has been developed by chemical bath deposition method. The objective to study growth kinetics, physical, microscopic, compositional, optical, electrical and structural changes. Cd1-xZnxSe have been deposited on non-conducting glass substrate in tartarate bath containing Cd+2 and Zn+2 ions with sodium selenosulphate with an aqueous alkaline medium at 278 K. The quality and the thickness of the films are depends upon deposition temperature, deposition time and pH, etc. X-ray diffraction (XRD), atomic absorption spectroscopy, optical absorption, scanning electron microscopy and thermoelectric technique characterized the films. The XRD study indicates the polycrystalline nature in single cubic phase over whole range of composition. Analysis of absorption spectra gave direct type band gap, the magnitude of which increases non-linearly as zinc content in the film is increased and dc electrical conductivity at room temperature was found to decreases from 10(-7) to 10(-8) (Omega cm)(-1). All the films show n-type conductivity. The promising features observed are the formation of continuous solid solutions in a single cubic phase.

Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD

Characterization of MoSe2 thin film deposited at room temperature from solution phase - Hankare, P. P.; Patil, A. A.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Manikshete, A. H.; Mulla, Imtiaz S. (Journal of Crystal Growth, 2008)
A simple, low-temperature method has been developed to synthesis molybdenum diselenide semiconductor thin films, based on the chemical reaction of conlplexed ammonium molybdate, hydrazine hydrate and sodium Selenosulphate in aqueous alkaline medium. The deposition parameter of the MoSe2 thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption and electrical measurements. The deposited film was found to be polycrystalline in hexagonal form. The direct band gap `E-g' for the film was found to be 1.43eV and electrical conductivity in the order of 10(-2)(Omega cm)(-1) with n-type conduction mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from solution; Inorganic compound; Polycrystalline deposition; Semiconducting materials; X-ray diffraction

Synthesis, characterization of chemically deposited indium selenide thin films at room temperature - Asabe, M. R.; Chate, P. A.; Delekar, S. D.; Garadkar, K. M.; Mulla, Imtiaz S.; Hankare, P. P. (Journal of Physics and Chemistry of Solids, 2008)
Polycrystalline In2Se3 semiconducting thin films were prepared by using relatively simple chemical bath deposition method at room temperature by the reaction between indium chloride, tartaric acid, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium. Various preparative conditions of thin film deposition are outlined. The as grown films were found to be transparent, uniform, well adherent and red in color. The films were characterized using X-ray diffraction (XRD), scanning electron microscopy, atomic absorption spectroscopy and energy dispersive atomic X-ray diffraction (EDAX). The XRD analysis of the film showed the presence of polycrystalline nature with hexagonal crystal structure. SEM study revels that the grains are homogenous, without cracks or pinholes and well covers the glass substrate. The optical absorption and electrical conductivity was measured. The direct optical band gap value for the films was found to be of the order of 2.35eV at room temperature and have specific electrical conductivity of the order of 10(-2) (Omega cm)(-1) showing n-type conduction mechanism. The utility of the adapted technique is discussed from the view-point of applications considering the optoelectric and structural data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Semiconductor

Magnetic, dielectric and complex impedance spectroscopic studies of nanocrystalline Cr substituted Li-ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Garadkar, K. M.; Sasikala, R.; Tripathi, A. K.; Mulla, Imtiaz S. (Journal of Magnetism and Magnetic Materials, 2010)
Nanocrystalline Li0.5Fe2.5-xCrxO4 (2.5 <= x >= 0) ferrites were prepared by a sol-gel autocombustion route. X-ray diffraction was employed to confirm the cubic spinel phase formation of the ferrites. The lattice parameter decreases with increase in Cr content. The saturation magnetization, coercivity and remanance were studied as a function of Cr content. The dielectric constant and dielectric loss were measured as a function of frequency in the frequency range 20 Hz-1 MHz. Frequency dependence of dielectric constant shows dielectric dispersion due to the Maxwell-Wagner type of interfacial polarization. In order to understand the conduction mechanism, complex impedance measurements were carried out. The substitution of chromium plays an important role in changing the dielectric and magnetic properties of lithium ferrites. (C) 2010 Published by Elsevier B.V.
Keywords: Complex impedance; dielectric response; Ferrites; Magnetic hysteresis; Sol-gel synthesis; X-ray diffraction

Synthesis and characterization of nanocrystalline zinc substituted nickel ferrites - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Sasikala, R.; Tripathi, A. K.; Garadkar, K. M. (Journal of Alloys and Compounds, 2010)
Nanocrystalline zinc substituted nickel ferrites, Ni(1-x)Zn(x)Fe(2)O(4) (0.0 <= x <= 1.0) have been prepared by citrate gel auto-combustion method. The effect of zinc ion content on structural, electrical transport and magnetic properties has been studied. The X-ray diffraction (XRD) pattern revealed that, all the compositions possess single-phase spinel structure. The nano-sized grain structure formation was confirmed by transmission electron microscopy (TEM). The dc electrical resistivity shows the samples are semiconducting in nature. The magnetic measurements showed that the composition Ni(0.6)Zn(0.4)Fe(2)O(4) has maximum saturation magnetization (M(s)) while high coersivity (Hc) for ZnFe(2)O(4). Thermoelectric power measurement study showed that the compounds, with x <= 0.4 are p-type and for x > 0.4 behaves n-type conduction mechanism. (C) 2010 Published by Elsevier B.V.
Keywords: Electron microscopy; Magnetic; Sintering; X-ray diffraction

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.

Chemical deposition of CuInSe2 thin films by photoelectrochemical applications - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2012)
Copper indium diselenide films have been synthesized by chemical bath deposition method. The configuration of fabricated cell is n-CuInSe2|NaOH (1 M) + S (1 M) + Na2S (1 M)|C-(graphite). The photoelectrochemical cell characterization of the films is carried out by studying current-voltage characteristics in dark, capacitance-voltage in dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that CuInSe2 thin films are n-type conductivity. The junction ideality factor is found to be 3.81. The flat band potential is found to be 0.763 V. The barrier height value is found to be 0.232 eV. The study of power output characteristic shows open circuit voltage, short circuit current, fill factor and efficiency are found to be 310 mV, 20 mu A, 42.12% and 0.82%, respectively. Photoresponse shows lighted ideality factor which is 2.92. Spectral response shows the maximum current observed at 650 nm. (C) 2011 Published by Elsevier B.V.
Keywords: Chemical bath deposition; Flat band potential; Photo response; Power output; Spectral response

Photocatalytic degradation of phosphamidon using Ag-doped ZnO nanorods - Korake, Prakash V.; Sridharkrishna, R.; Hankare, P. P.; Garadkar, K. M. (Toxicological and Environmental Chemistry, 2012)
The photocatalytic degradation of the organo-phosphorous pesticide phosphamidon at low concentration in aqueous solution on Ag-doped ZnO nanorods was investigated. Nanosized Ag-doped ZnO rods were synthesized by using a microwave assisted aqueous method. High molecular weight polyvinyl alcohol was used as a stabilizing agent. Composition and structure were investigated using energy-dispersive X-ray spectroscopy (EDAX) and X-ray diffraction (XRD). The XRD pattern reveals that ZnO nanorods are of hexagonal wurtzite structure. The average crystallite size calculated from Scherrer's relation was found to be 30 nm. The effects of catalyst loading, pH value, and initial concentration of phosphamidon on the photocatalytic degradation efficiency using Ag-doped ZnO nanorods as a photocatalyst have been discussed. The results revealed that Ag-doped ZnO nanorods with a diameter of 30 nm showed highest photocatalytic activity at a surface density of 1 g dm(-3). The catalyst doped with 0.2 mol% Ag is effective for the degradation of phosphamidon with visible light. This opens a new possibility to decompose pesticides that are present in wastewater.
Keywords: Ag-doped zinc oxide; phosphamidon; Photocatalysis; Photodegradation

Structural and surface morphological properties of chemically deposited Mo0.5W0.5S2 thin film - Patil, A. A.; Hankare, P. P.; Gaikwad, A. B.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2012)
Preparation of layered type semiconductor Mo0.5W0.5S2- thin films has been successfully done by using chemical bath deposition method. Objective of the studies are related to structural, optical, morphological and electrical properties of the thin films. The preparation method is based on the reaction between tartarate complex of Mo and W with thiourea in an aqueous alkaline medium at 363 K. X-Ray diffraction reveals a polycrystalline film composed of both MoS2 and WS2 phases. The optical study shows that the band gap of the film is 1.6 eV. Electrical conductivity is high which is in the order of 10(-3)-10(-2) (Omega cm)(-1).